2021
DOI: 10.1016/j.ejmech.2021.113814
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin-based PROTACs as pan-coronavirus antiviral agents

Abstract: Indomethacin (INM), a well-known non-steroidal anti-inflammatory drug, has recently gained attention for its antiviral activity demonstrated in drug repurposing studies against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Although the mechanism of action of INM is not yet fully understood, recent studies have indicated that it acts at an early stage of the coronaviruses (CoVs) replication cycle. In addition, a proteomic study reported that the anti-SARS-CoV-2 activity of INM could be also ascr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 50 publications
0
57
1
Order By: Relevance
“…This illustrates that this prototypic CDK9-targeted PROTAC, which exerts the intended degradative mechanism as experimentally verified, presents a measurable advantage over the non-PROTAC parental inhibitor. Notable, a similarly sized five-fold increase in activity was recently described for anti-coronaviral PROTACs based on indomethacin [ 42 ], indicating that this magnitude is easily achievable by converting an inhibitor to its corresponding PROTAC, an approach that is still open for optimization as a focus of our continued studies on antiviral options against human pathogenic viruses, including HCMV.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This illustrates that this prototypic CDK9-targeted PROTAC, which exerts the intended degradative mechanism as experimentally verified, presents a measurable advantage over the non-PROTAC parental inhibitor. Notable, a similarly sized five-fold increase in activity was recently described for anti-coronaviral PROTACs based on indomethacin [ 42 ], indicating that this magnitude is easily achievable by converting an inhibitor to its corresponding PROTAC, an approach that is still open for optimization as a focus of our continued studies on antiviral options against human pathogenic viruses, including HCMV.…”
Section: Resultsmentioning
confidence: 93%
“…For this reason, our prioritized approach with currently synthesized PROTACs will be directed to multiprotein complexes essential for virus replication. Despite these potential benefits, only telaprevir-based PROTACs active against the hepatitis C virus and indomethacin-derived PROTACs with anti-coronavirus activity have been reported on so far [ 42 , 55 ]. Taken together, data of this study underline that PROTACs harbor untapped, possible game-changing potential in regard to antiviral drug development, so that skillful procedures of PROTAC synthesis and a structure–activity relationship may guarantee further success in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…Their PROTAC demonstrated robust viral spike protein receptor binding domain (RBD) degradation capabilities in human cells and the ability to inhibit infection-competent viral production. Recently Desantis et al revealed the first indomethacin-based small molecular PROTAC 157 as a pan-coronavirus antiviral agent that targets a host protein (prostaglandin E synthase type 2) rather than a viral one for degradation with the advantage of overcoming resistance issues. In 2020, Haniff et al have designed a ribonuclease targeting chimera (RIBOTAC) 158 that recruits a cellular ribonuclease to degrade the viral genome leading to inhibition of SARS-CoV-2 frameshifting.…”
Section: Mechanisms Of Resistance In Targeted Protein Degradationmentioning
confidence: 99%
“…Plaque reduction assays (PRA) with different CoVs were performed as previously described ( Desantis et al, 2021 ). For SARS-CoV-2, Vero E6 cells were seeded at a density of 1 × 10 5 cells per well in 24-well plates and the next day, were infected with 80 Plaque Forming Unit (PFU) per well of SARS-CoV-2 (SARS-CoV-2/NL/2020 strain).…”
Section: Methodsmentioning
confidence: 99%